PSSFSS—An Open-source Code for Analysis of Polarization and Frequency Selective Surfaces - Simon, Peter S. (Applied Computational Electromagnetics Society journal, 2024)
The open-source code PSSFSS for analysis and design of polarization selective surfaces (PSSs), and frequency selective surfaces (FSSs) is presented, beginning with an introduction to the Julia programming language in which the code is written. Analysis methods and algorithms used in PSSFSS are described, highlighting features of Julia that make it attractive for developing this type of application. Usage examples illustrate the code’s ease of use, speed, and accuracy.